Clinical Correlates of Ambulatory Blood Pressure Phenotypes at a Tertiary Care Hospital in Turkey - Siyar Erdogmus; Sim Kutlay; Zeynep Kendi Celebi; Tolga Aydın; Damla Ors Sendogan; Gizem Kumru; Kenan Keven; Gokhan Nergizoglu; Sehsuvar Erturk; Sule Sengul (Karger Publishers, 2018)
Background/Aims: Hypertension and its complications are major public health issues worldwide due to their association with high cardiovascular morbidity and mortality. Despite significant progress in health, the prevalence of hypertension is increasing. Ambulatory blood pressure monitoring (ABPM) is becoming increasingly important for the management of hypertension. In this study, we aimed to investigate the clinical and laboratory correlates of ambulatory blood pressure (ABP) phenotypes at a tertiary care hospital in Turkey. Methods: The characteristics of 1053 patients were retrospectively obtained from the hospital database. Hypertension was defined as patients with office blood pressure (BP) ≥140/90 mmHg and/or previously diagnosed hypertension and/or the use of antihypertensive medication. According to the office BP and ABPM results patients were identified namely: (1) sustained normotensive (SNT) patients (both office BP and ABPM were normal), (2) sustained hypertensive (SHT) patients (both office BP and ABPM were high), (3) masked hypertensive (MHT) patients (office BP were normal, but ABPM were high), (4) white coat hypertensive (WCHT) patients (office BP were above limits, but ABPM were normal). Results: A total of 1053 patients were included to the study (female/male: 608/445 and mean age 55 ± 15 years). The mean age of patients with hypertension was significantly higher than without hypertension (p< 0.0001). Hypertension was more frequent in females (p=0.009). The rates of history of diabetes mellitus (DM), hyperlipidemia (HL), and chronic kidney disease (CKD) were higher in patients with hypertension (p< 0.0001). Among patients with hypertension (n=853, 81%), ABPM results showed that 388 (45%) of patients had SHT, 92 (11%) had MHT, and 144 (17%) had WCHT, whereas 229 (27%) had SNT. Patients with MHT were significantly older than patients with SNT (p=0.025). The prevalence of SHT was higher in men than in women, whereas the prevalence of WCHT was higher in women than in men (p< 0.0001). There was no significant difference between 4 groups with regard to body mass index (p=0.142), a history of DM (p=0.189) and smoking status (self-reported) (p=0.306). Patients with SHT had the highest prevalence of history of hypertension, HL and CKD (p< 0.0001). Among patients without hypertension, 26 (13%) of patients had MHT and none of those patients was on antihypertensive treatment. Conclusion: Potential usages of ABPM in Turkey may include screening of high risk individuals who have traditional cardiovascular risk factors. It also provides clinicians valuable information on abnormal ABP phenotypes. Future studies are needed to clarify the risk factors of different ABP phenotypes and to evaluate the role of ABPM on detection and control of hypertension.